A DIRECT BONDING TECHNIQUE VERSUS AN INDIRECT BONDING TECHNIQUE - AN IN VIVO ANALYSIS - BHARGAVA, ANANYA; BHARGAVA, APOORVA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of this study were to compare the clinical performance of an indirect versus a direct bonding technique in a split mouth study design and to develop a reproducible and cost efficient technique for indirect bonding for clinical use. Methods: This comparative study was conducted on Twelve patients (212 teeth; 106 each in direct and indirect group) who reported to the Department of Dentistry at Ruxmaniben deepchand gardi medical college, Ujjain, Madhya Pradesh. Transbond XT (3M Unitek) adhesive and primer were used to bond the brackets onto the teeth in both the direct and indirect bonding groups using split mouth study design. Transfer trays constructed using Thermal glue matrix applied through hot glue gun for indirect bonding. The clinical performance was assessed for 6 months. Results: In the 1st month was a failure of one lower 2nd premolar bracket from the indirect bonding group (p=1.00). There on in the subsequent months there were no failures for 6 months. The study showed no statistically significant differences in clinical performance in both group (p=NS). Conclusion: The failure rates for both the indirect and direct bonding techniques in this study were the same. Statistically, there was no significant difference between the two groups. The indirect bonding technique used in this study was found to be an effective and efficient means of bonding orthodontic brackets. Transbond XT and thermal glue matrix found to be suitable choice for use in indirect bonding technique for clinical use.